Dragons and lizards - Barrett, Norman S. (New York : Watts, 1991)
A look at the feeding habits, reproductive behavior, and other life functions of lizards living in desert, tropical, and temperate environments.
6.2
3-5.
3-6
Keywords: Lizards; Lizards